GEORGIA: ECONOMIC POLICY AFTER THE “REVOLUTION OF ROSES” - KANDELAKI, Otar (CENTRAL ASIA AND THE CAUCASUS, 2004)
In 1989, influential financial and political organizations and well-known economists agreed upon the main lines of reform in economic policy, which became known as the Washington Consensus. Its ideas had a significant impact on the way of thinking and course of action in the countries of Eastern Europe and in the Soviet Union, although initially that policy was intended not for a restructuring of the postsocialist countries, but for already functioning markets, so that in some respects it proved to be inad-equate to the needs of the transition period. The Washington Consensus stressed the importance of liberalization, privatization, the opening up of postsocialist economies, and the necessity of maintaining fiscal discipline. But that approach did not take into account a number of important elements required for systemic transformation, stabilization and growth. This includes institution building, an improvement of corporate governance in the state sector prior to privatization, and a review of the state’s role in the economy, but without its complete withdrawal from economic activities (as the record of many countries shows, with excessive deregulation a society based on the principles of liberalism cannot prevent an increase in social inequity). The assumption that emerging market forces can quickly replace the government in the field of institutional development, investment in human capital and development of the infrastructure resulted in a sharp contraction of the economy and growing social tensions. The lack of a basic market structure and financial intermediaries impeded accumulation and worsened the allocation of savings. Thus, the lack of proper control over the emerging market in the post socialist countries and the absence of such key organizations as investment banks, stock exchanges, security and control agencies, etc., created problems which could not be resolved by liberalization or privatization. Employment in these countries fell sharply. Since their economic systems had formerly operated with a labor shortage, they had no social security system protecting against unemployment and were obliged to build up such a system from scratch. The need to manage the institutional aspects of the transition process was recognized and taken into account only at later stages. Georgia has learned from its own experience that even a sound economic basis (i.e., a balanced budget and current account, low inflation, a steady currency, free trade and a developed private sector) cannot ensure growth unless it is supported by an appropriate institutional setup. Much is being said today about the shortcomings of the set of measures recorded in the Washington Consensus and about the advantages of “gradualism” compared with “shock therapy.” However, it is rarely taken into account that the most destructive effect on the transition economy was exerted not by these measures themselves, but by their half-hearted implementation. That is why in many countries, including Georgia we saw the emergence of an essentially corrupt and destructive combination of the private property system and a quasi-market, which means a lack of normal competition and of a level playing field for business activity. That resulted in a sharp stratification of society and large disparities in consumption levels. In Georgia, all these processes created a prerevolutionary situation.